Akkermansia muciniphila attenuates association between specific metal exposures during pregnancy and depressive symptoms in late childhood - Vishal Midya; Kiran Nagdeo; Jamil M. Lane; Libni A. Torres-Olascoaga; Gabriela Gil Martínez; Megan K. Horton; Nia McRae; Inessa Lopez; Julio Landero; Chris Gennings; Martha Maria Téllez-Rojo; Robert O. Wright; et al. (iScience)
Summary: Emerging research suggests that exposures to metals during pregnancy and consequent disruptions in gut microbiome (GM) are associated with depressive disorders in childhood. Akkermansia muciniphila, a GM bacteria, has been studied for its potential antidepressant effects. However, its role in influencing the association between prenatal metal exposures and depressive symptoms during childhood is unknown. Leveraging a well-characterized pediatric birth cohort and its microbiome substudy (n = 112), we investigated whether a certain subgroup of children at 9-11-year-of-age (characterized by a specific pattern of prenatal exposure to groups of metals or metal-clique) had worsened depressive symptoms and if the presence of A.muciniphila in GM modifies this association. A subgroup of children characterized by the prenatal metal-clique signature of zinc-chromium-cobalt had significantly increased depression scores; however, within that subgroup, children with A.muciniphila had much lower depression scores than those without A.muciniphila in the GM. Our analysis provides exploratory evidence hypothesizing A.muciniphila as an intervention attenuating the effect of prenatal metal-exposures-associated depressive disorders in late childhood.